THE SAME GOES FOR ORGANIZING ELEMENTARY SCHOOL NATIVE LANGUAGE CLASSES SPECIFICITY (ResearchJet Journal of Analysis and Inventions, 2021)
The article in the section describes the advantages and problems of non-traditional lessons in language lessons for primary school, the use of modern teaching techniques in educational systems, the definition of methods of teaching students who provide multimedia services.